O papilomavírus humano em meninas de uma unidade de saúde do município de Vitória : avaliação de um potencial grupo de risco - Sartori, Mariana Penha de Nadai (2012)
Human papillomavirus (HPV) is the most common sexually transmitted virus in the world, being a cause of genital warts (Low-Risk HPV) and cervical cancer (High-Risk HPV). The virus is found in sexually active adults and adolescents, however, it has been detected in girls victims of sexual violence or not. The worldwide incidence of HPV is increasing in girls and viral transmission modes are still not completely defined. Currently, HPV prevention is based on two available vaccines only for the age group 9-26 years old and there are no available vaccines or other prevention methods for patients under nine years old, since it is not considered a risk group by competent health authorities. There are no studies of the Espírito Santo state about the HPV prevalence in girls under 9 years old and therefore their importance is not established. Because of these reasons, the aim of this study was to detect HPV in girls under nine years old, as well as finding possible routes of transmission in order to provide information for the development of preventive practices for this risk group. A total of 43 samples extracted from girls under 9 years old were analyzed using PCR, RFLP and DNA sequencing methods for viral detection and typing. Human papillomavirus was detected in 13.9% of patients, mostly low risk genotypes. Clinical and personal evaluation suggested that girls were infected by horizontal transmission and via fomites. Due to our findings, we propose that HPV infection prevention through vaccination should be extended to girls under 9 years old, especially in specific high risk populations.